Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The availability of dimensions of creative leadership among secondary school principals in Wadi Al-Dawasir and its relationship to institutional excellence from the teachers' point of viewMrs. Mitab Fahad Matruk Al-Dossary2. The Degree of Transcendental Leadership Practice Among School Principals in The Directorate of Education, Al-Qasr/ Karak districtMrs. Widad Salim Al-Lassasmeh3. The reality of the educational role of the secondary school in the educational region of Hail in achieving the social goals of sustainable development from the point of view of its teachersMrs. Nawadir Murbih Alzabanii , Dr. Najla' Muhamad Alhadif4. The level of parents' awareness of the importance of kindergarten in Hafar Al-Batin GovernorateMrs. Rawan Ali Al-Harbi5. Self-efficacy beliefs and their impact on the ambition of students of higher education institutions in the Sultanate of Oman from their point of viewMrs. Sabra Saif Ahmed Alharrasi , Prof. Mastura Badzis6. Assessment and Diagnosis barriers for Students with Communication Disorders from the Prospective of Speech Specialists in Al-Madinah Al-MunawwarahMrs. Shatha Sabir Toukhi , Dr. Ghadah Ghazi Alharbi7. Personal Traits of Teachers and Their Relationship to Their Job Satisfaction in The Sultanate of OmanMr. Hilal Shamis Hamad Al-Thohli , Mrs. Nasra Saleh Abdullah Al-Abri
Keywords: Journal of Educational and Psychological Sciences